Soy protein isolate added to vacuum-packaged chorizos: effect on drip loss, quality characteristics and stability during refrigerated storage - Porcella, Marcela I.; Sanchez, Guillermo; Vaudagna, Sergio Ramon; Zanelli, Marta L.; Descalzo, Adriana Maria; Meichtri, Lelis Hemil; Gallinger, Maria M.; Lasta, Jorge Augusto (Elsevier, 2019)
Chorizo is a raw sausage, which is manufactured with beef, pork meat and pork fat, additives and spices. In Argentina, the expenditure of chorizo is through butchery and supermarkets where the product can be found packaged in both polyethylene films and vacuum sealed pouches. In the latter type of packaging an appearance problem has been detected in relation to drip loss. The aim of the work was to solve such problem through the incorporation of soy protein isolate (SPI). The sensory, microbiological and chemical stability of the product and its drip loss during a storage period of 14 days were studied. By adding a 2.5% SPI, the drip loss was prevented without introducing any change in the flavour, aroma and juiciness characteristics of the product. These sensory attributes were kept stable during the storage period studied. Chemical composition, oxidative and microbiological stability were not affected by the addition of SPI during the storage period, being similar for added and non-added SPI samples. Finally, SPI can be used in chorizos to improve their overall appearance during refrigerated storage while the product quality characteristics are not altered.